PERAN KOMUNIKASI ORGANISASI DALAM MENDUKUNG PENGEMBANGAN PROGRAM PENDIDIKAN PADA KOMUNITAS HAGA PENDIDIKAN ONO NIHA - Citra Nanda Purba; Evika Kartika Sari Lawolo; Nova Novita Siregar; Sherina Silaban; Fauzi Kurniawan; Anifah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
ABSTRACT This study aims to analyze the role of organizational communication in supporting the development of educational programs within the Haga Pendidikan Ono Niha (HPON) community. Conducted using a descriptive qualitative approach, the research gathers data through in-depth interviews with the HPON leader and supporting documentation. Findings indicate that HPON employs a democratic communication pattern that ensures equal opportunities for members to express ideas, opinions, and criticisms. The main communication dynamic is the emergence of differing viewpoints caused by variations in perspectives, communication styles, information gaps, and interpersonal factors. When consensus cannot be reached through deliberation, the organization applies a voting mechanism to maintain fairness and collective decision-making. Effective communication is found to strengthen coordination, enhance participation, and support the implementation of educational activities, particularly in outreach programs such as university entrance guidance. The study concludes that organizational communication plays a strategic role in improving program effectiveness and group cohesion while highlighting the need to strengthen interpersonal communication skills and deliberative processes within the community.